A new Specklinia (Orchidaceae: Pleurothallidinae) from Costa Rica and Panama - Bogarín Chaves, Diego Gerardo (2013)
A new species of Specklinia from the Cordillera de Talamanca in southern Costa Rica and western Panama is described and illustrated. Specklinia absurda most closely resembles Specklinia fuegi. It differs from that species in the pendent, single flowered inflorescence, whitish yellow sepals with red-pink veins and yellow apex, red petals with translucent margins, pandurate-trilobed, unguiculate lip with a distinct papillose isthmus below the anterior lobe, and reniform, erose, erect lateral lobes, with a Y-shaped thickened, hirsutulous apical callus. The affinities of this species to other Specklinia species are discussed.